2012
DOI: 10.5194/acp-12-1649-2012
|View full text |Cite
|
Sign up to set email alerts
|

Identification and quantification of organic aerosol from cooking and other sources in Barcelona using aerosol mass spectrometer data

Abstract: Abstract. PM1 (particulate matter with an aerodynamic diameter <1 μm) non-refractory components and black carbon were measured continuously together with additional air quality and atmospheric parameters at an urban background site in Barcelona, Spain, during March 2009 (campaign DAURE, Determination of the sources of atmospheric Aerosols in Urban and Rural Environments in the western Mediterranean). Positive matrix factorization (PMF) was conducted on the organic aerosol (OA) data matrix measured by an aer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

107
544
7
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 506 publications
(688 citation statements)
references
References 68 publications
107
544
7
1
Order By: Relevance
“…Fourth factor was found to contain elevated relative signal at m/z's 29, 60 and 73, suggesting the presence of wood combustion, likely from local domestic heating (Lanz et al, 2007;Aiken et al, 2008). That factor also contains elevated signal at m/z's 41, 43 and 55, which has been associated with cooking OA (COA), an important source of POA in urban environments like Zurich, Barcelona and Manchester (Lanz et al, 2007;Allan et al, 2010;Mohr et al, 2012). Mohr et al (2012) demonstrated that food charbroiling mass spectrum differs from HOA due to the oxygen-containing ions in the m/z's 43, 55 and 57, typical from fatty acids.…”
Section: Characterization Of Oa Components Acsm-pmf Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth factor was found to contain elevated relative signal at m/z's 29, 60 and 73, suggesting the presence of wood combustion, likely from local domestic heating (Lanz et al, 2007;Aiken et al, 2008). That factor also contains elevated signal at m/z's 41, 43 and 55, which has been associated with cooking OA (COA), an important source of POA in urban environments like Zurich, Barcelona and Manchester (Lanz et al, 2007;Allan et al, 2010;Mohr et al, 2012). Mohr et al (2012) demonstrated that food charbroiling mass spectrum differs from HOA due to the oxygen-containing ions in the m/z's 43, 55 and 57, typical from fatty acids.…”
Section: Characterization Of Oa Components Acsm-pmf Factorsmentioning
confidence: 99%
“…That factor also contains elevated signal at m/z's 41, 43 and 55, which has been associated with cooking OA (COA), an important source of POA in urban environments like Zurich, Barcelona and Manchester (Lanz et al, 2007;Allan et al, 2010;Mohr et al, 2012). Mohr et al (2012) demonstrated that food charbroiling mass spectrum differs from HOA due to the oxygen-containing ions in the m/z's 43, 55 and 57, typical from fatty acids. Moreover, in the food charbroiling mass spectra the m/z 43 presents higher relative signal than 41.…”
Section: Characterization Of Oa Components Acsm-pmf Factorsmentioning
confidence: 99%
“…The results of PMF illustrate that rBC-and HOA-rich factors accounted for about 60 and 20 wt % of rBC with a thin coating, respectively, and the rBC-rich factor contributed about 82 wt % of the freshly emitted rBC from traffic, similar to previous observations in the roadside environment . The COA factor is commonly observed in urban areas (Allan et al, 2010;Mohr et al, 2012) but its mixing with ambient rBC is seldom reported. The absence of a COA factor in rBC-containing particles highlights the fact that emissions of rBC from modern kitchens and the mixing of rBC and COA through particle coalescence were negligible in this study.…”
Section: Conclusion and Atmospheric Implicationsmentioning
confidence: 99%
“…This approach is a simplistic approximation, but the lower limit appears to be reasonable given that the diurnal cycles and spectral characteristics of CIOA are consistent with previous studies. In addition, comparison of the CIOA concentration against that predicted from the amount of organic mass measured by the AMS at m/z 55 following Mohr et al [2011] indicates that approximately 75% of CIOA is from cooking sources (see section D of the supporting information for the details of this comparison). A higher percentage up to almost 100% is also possible given the uncertainties in the comparison.…”
Section: Evaluation Of Primary Organic Aerosol Emission Ratios With Ementioning
confidence: 99%
“…For HOA, O : C is relatively high (0.14) but not out of the range of previously reported values. For instance, O : C values as low as 0.02 (Riverside, CA) and 0.03 (Barcelona) [Docherty et al, 2011;Mohr et al, 2011] and as high as 0.16 (Mexico City) and 0.17 (Beijing) have been reported for HOA components [Aiken et al, 2009;Huang et al, 2010]. The diurnal cycle of HOA is similar to that of EC (and rBC) with a peak between 13:00 and 14:00 PDT (local time), and HOA and EC (and rBC) show high correlation (see Table D-1 in the supporting information and section 3.3 below).…”
Section: Source Apportionment Of Organic Aerosol Mass By Positive Matmentioning
confidence: 99%